Overlap between attention-deficit hyperactivity disorder and neurodevelopmental, externalising and internalising disorders: separating unique from general psychopathology effects. (January 2021) - Du Rietz, Ebba; Pettersson, Erik; Brikell, Isabell; Ghirardi, Laura; Chen, Qi; Hartman, Catharina; Lichtenstein, Paul; Larsson, Henrik; Kuja-Halkola, Ralf
Abstract : Background: Although attention-deficit hyperactivity disorder (ADHD) is classified as a neurodevelopmental disorder in the latest diagnostic manuals, it shows phenotypic and genetic associations of similar magnitudes across neurodevelopmental, externalising and internalising disorders. Aims: To investigate if ADHD is aetiologically more closely related to neurodevelopmental than externalising or internalising disorder clusters, after accounting for a general psychopathology factor. Method: Full and maternal half-sibling pairs ( N = 774 416), born between 1980 and 1995, were identified from the Swedish Medical Birth and Multi-Generation Registers, and ICD diagnoses were obtained from the Swedish National Patient Register. A higher-order confirmatory factor analytic model was fitted to examine associations between ADHD and a general psychopathology factor, as well as a neurodevelopmental, externalising and internalising subfactor. Quantitative genetic modelling was performed to estimate the extent to which genetic, shared and non-shared environmental effects influenced the associations with ADHD. Results: ADHD was significantly and strongly associated with all three factors ( r = 0.67–0.75). However, after controlling for a general psychopathology factor, only the association between ADHD and the neurodevelopmental-specific factor remained moderately strong ( r = 0.43, 95% CI = 0.42–0.45) and was almost entirely influenced by genetic effects. In contrast, the association between ADHD and the externalising-specific factor was smaller ( r = 0.25, 95% CI = 0.24–0.27), and largely influenced by non-shared environmental effects. There remained no internalising-specific factor after accounting for a general factor. Conclusions: Findings suggest that ADHD comorbidity is largely explained by genetically influenced general psychopathology, but the strong link between ADHD and other neurodevelopmental disorders is also substantially driven by unique genetic influences.